VIZUAL SUPPORT OF ALGORITHMIC PREPARATION OF FUTURE TEACHERS OF MATHEMATICS IN THE CONDITIONS OF IKT - Voloshinov, C.A. (Journal of Information Technologies in Education (ITE), 2010)
The questions of the use of vizualizators are examined in the article, in particular module environment of demonstration of the integrated environment of study of course of «Basis of algoritmization and programming» (http://weboap.ksu.ks.ua), developed in RIIT of the Kherson state university, for the study of course of programming in higher school.